GINGIVECTOMY OF GINGIVAL ENLARGEMENT IN ORTHODONTIC PATIENT - Sopiatin, Siti (Cakradonya Dental Journal, 2021)
Gingival enlargement is a common condition in patients who are using fixed orthodontic appliances. In certain patients, the use of fixed orthodontic appliances can lead to enlargement of the gingiva which can make it difficult to maintain oral hygiene, causing inflammation of the gingiva and disrupting aesthetic function. A female patient aged 18 years came to the Periodontics Clinic of the Padjadjaran University Dental Hospital with the main complaint of enlarged gingiva in all regions of the mandible since 1 year ago, no history of shrinkage, and no pain. At the time of the intra oral examination, the maxillary gingiva also appeared to cover part of the tooth surface although it did not appear to be swollen, but it caused the teeth to appear shorter. Patient is using fixed orthodontic appliance since 3 years ago. Gingivectomy is effective in treating gingival enlargement in patients who are using fixed orthodontic appliances. The therapy aims to remove gingival pockets, prevent inflammation and advanced periodontal disease, and restore aesthetic function.